PENGARUH EARNING PER SHARE DAN PRICE TO BOOK VALUE TERHADAP HARGA SAHAM PT. PEMBANGUNAN PERUMAHAN, TBK - Diah Juliningtias; Sunartiyo (Jurnal Ekonomi dan Industri, 2019)
This research aim to to check influence,monunt earning per share and price to book value to price Share of PT. Pembangunan Perumahan, TBK. Methode analyse data used in this research is methode of dobled linier represi to anticipate influence frome some Independent variable either through persial and also by simultan to variable dependent. This finding yield that by simultan is inflnence af Independent variable (earning per share and price to book value to price Share) having on effect on positif and significan to variable dependence (Share Price)